2020
DOI: 10.1007/978-3-030-58858-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Forming and Assessing Student Teams in Software Engineering Courses

Abstract: In software development projects, working in teams is essential. Therefore, software engineering courses often require the students to be working in teams to learn about team work behaviors and practices. The instructors of software engineering courses are presented with several challenges when teaching courses that require teamwork. For example, how to form high-performing student teams, and how to assess their work. The aim of this study is to evaluate whether there are differences in performance whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Løvold et al [27] found that student-formed teams performed slightly better than instructor-formed, advantaging from already knowing each other and how they work together. However, mixing the two approaches, allowing students to submit their team preferences for the instructor to base team formation on, could give the students ownership and include social benefits from the self-assigned approach, while at the same time ensuring balanced teams regarding the project needs [33].…”
Section: Diversity In Software Development Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Løvold et al [27] found that student-formed teams performed slightly better than instructor-formed, advantaging from already knowing each other and how they work together. However, mixing the two approaches, allowing students to submit their team preferences for the instructor to base team formation on, could give the students ownership and include social benefits from the self-assigned approach, while at the same time ensuring balanced teams regarding the project needs [33].…”
Section: Diversity In Software Development Teamsmentioning
confidence: 99%
“…Research on team composition in agile software engineering capstone courses has highlighted the challenges faced by instructors in creating well-balanced and effective teams [11,27]. To address this, algorithmically supported systems like TEASE have been developed to assist instructors in team composition, resulting in better mean project priority and reduced time for team formation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Team formations can be shaped by academic performance of students, or perceptions of lecturers, that may result in human-dependent and error-prone processes. Students prefer to forming their groups without the intervention of a lecturer [27]. But selfformed groups by students may impact some inexperienced students, who cannot learn from their experienced peers [28].…”
Section: Agile Software Engineers Stick Together (Asest)mentioning
confidence: 99%
“…The three main components (group, formation, project and evaluation) are identified and discussed in this section, and summarized in Figure 1. Even though 55% of instructors require students to complete a group assignment in GIS&T courses (Mathews & Wikle, 2019), there is scant literature on group formation, even for software engineering courses (Løvold, Lindsjørn, & Stray, 2020). Therefore, the question how groups can be formed requires further attention.…”
Section: A T Yp Ology Of Coll Abor Ative G Is Prog R Amming Cour S E ...mentioning
confidence: 99%